Peran Kepala Sekolah dalam Meningkatkan Mutu Pendidikan - Juliantoro, Mohamad (Jurnal al Hikmah, 2017)
The changing of the era that continues to dynamic, demanding the improvement of the quality of school institutions must be done. It is considered mandatory for the entire unit within the institution to maintain its existence. The principal as a leader (leader) who holds the progress and retreat of a school should be able to take steps in improving the quality of education. The quality of education will be achieved, if supported by all components of education are well-organized. In this regard, the researcher focuses on: 1) How is the principals role as Educator in improving the quality of education in SMPN 3 Peterongan Darul Ulum Jombang and Islamic Junior High School Baitul Izzah Nganjuk ?, 2). What is the role of the principal as a Manager in improving the quality of education in SMPN 3 Peterongan Darul Ulum Jombang and Islamic Junior High School Baitul Izzah Nganjuk ?, 3). What is the role of the principal as an Administrator in improving the quality of education in SMPN 3 Peterongan Darul Ulum Jombang and Islamic Junior High School Baitul Izzah Nganjuk ?, 4). What is the role of the principal as Supervisor in improving the quality of education in SMPN 3 Peterongan Darul Ulum Jombang and Islamic Junior High School Baitul Izzah Nganjuk ?.this research uses qualitative naturalistic approach with multicasus study design, data collection is done by using deep interview technique, participant observation, and documentation. To avoid mistakes in this study, then examined the validity of data with peer discussion, data triangulation, and triangulation of data sources. Then the data is analyzed by using data analysis, that is; data reduction, data presentation, and conclusions.The findings of this study can be concluded, that the role of school principals in improving the quality of education as 1). educator 2). manager 3). administrator 4). supervisor